2022
DOI: 10.3390/ma15113987
|View full text |Cite
|
Sign up to set email alerts
|

Fractographic and Microhardness Evaluation of All-Ceramic Hot-Pressed and CAD/CAM Restorations after Hydrothermal Aging

Abstract: All-ceramic dental restorations have great advantages, such as highly esthetical properties, a less complex fabrication, and a similar abrasion resistance to enamel. Despite these advantages, ceramic materials are more prone to fracture due to their brittle microstructure. The main aim of this in vitro study was to determine the difference in hot-pressed and milled glass-ceramic mechanical properties such as fracture resistance and microhardness (VHN). Four types of ceramics, two hot-pressed and two milled, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Materials prepared and analyzed as working electrode in the electrolyte solution (5M H 2 SO 4 ) were investigated to determine their Vickers hardness [ 16 ]. This measurement is used to evaluate the defects or micro-cracks occurring after the introduction of electrode materials into the electrolyte solution.…”
Section: Resultsmentioning
confidence: 99%
“…Materials prepared and analyzed as working electrode in the electrolyte solution (5M H 2 SO 4 ) were investigated to determine their Vickers hardness [ 16 ]. This measurement is used to evaluate the defects or micro-cracks occurring after the introduction of electrode materials into the electrolyte solution.…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, different studies investigated the mechanical behavior of ZLS restorations by analyzing the material's physical properties, such as fracture toughness, flexural strength, elastic modulus, or hardness. The majority of in vitro studies have revealed that ZLS restorations exhibit better mechanical properties compared to lithium disilicate ceramics [13,[59][60][61] but worse properties compared to translucent or high-translucency zirconia [62]. Abu-Izze et al [63] conducted a study focusing on the fatigue strength of minimally invasive tabletop restorations.…”
Section: Mechanical Properties Of Zls Ceramic Systemsmentioning
confidence: 99%
“…Monolithic millable blocks provide the definitive restoration of single materials, unlike the multiple layering of the ceramic restoration. This results in higher material qualities, such as a high fracture toughness, hardness, acceptable esthetics, and minimal adjustments in the oral cavity, limiting the extent of ceramic fracture or chipping [ 3 , 4 ]. The improvement in the clinical performance of monolithic restorations may be attributed to the lack of differences in their flexural strength, modulus of elasticity, and thermal expansion coefficient, unlike multilayered ceramic restorations that are composed of several ceramic layers of different compositions [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%